Mechanics of materials - Riley, William F.; Sturges, Leroy D.; Morris, Don H. (New York : John Wiley and Sons, 1999)
This book is about: Analysis of stress; Analysis of Strain; material properties and stress-strain relationships; Axial loading applications and pressure vessels; Torsional loading of shafts; ...
Keywords: Engineering; Strength of materials; Structural analysis (Engineering); Strength of materials